PENYIDIKAN TINDAK PIDANA PORNOGRAFI MELAUI MEDIA SOSIAL FACEBOOK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DI DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU - Hardianti N, Ririn; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
One of the phenomenal case happening today is the distribute of pornographic images via facebook. Where is the account of facebook most often used as a place for the distribute the nude photo. That is not enough to distribute the pornography contain, but also write words that do not deserve to be spoken, and usually the perpetrators are also looking for an advantage over the distribute of nude photo with extortion by threatening the victim. It is certainly necessary role of law enforcement officials, especially the police in the investigations so that cases like this do not occur in the future. But the fact is happening is an investigator in the Sub Directorate of Special Criminal Investigation Directorate II Riau Police conduct an investigation only if the perpetrator is already clear only identity. So many cases are simply stalled until the investigation level only, surely this is an avenue for offenders to be free without any punishment.This type of research is classified in socio-juridical kind of research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Special Criminal Investigation Directorate Riau Police, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data and data tertiary, data collection techniques in this study with interviews, and review of the literature.From the research, there are three main things that can be inferred, first that the investigation of criminal pornography through social media facebook is still not running as it should be due to administrative processes such as arrest, detention, and seizure of evidence convoluted result in the investigation process takes a long time. Second, that the bottleneck is in need of experts that more than one person for expert unavailability of experts who master the technology and information so that the investigation to inquire experts should wait on the Police Headquarters of the Republic of Indonesia, facilities and infrastructure that support the investigation process, knowledge of the investigator of crimes against cyber crime investigators resulted in a lack of personnel compared to the number of cyber crime cases that occur, as well as public legal awareness is not optimal. Third, that the efforts made in overcoming obstacles criminal offense of pornography through social media facebook is to add to add human resources to master and understand the technology and information so that each region has an expert witness cyber-certified, the policy of the headquarters of the Police of the Republic of Indonesia to add facilities and infrastructure to support the process of investigation and to send police officers to participate in training or a course in understanding the cyber crime in developed countries to be applicable in the country of Indonesia.Keywords: Investigation - Crime Pornography - Facebook